Chemically Deposited Cubic Sns Photocathodes for Photoelectrochemical Water Splitting - Radhalayam, D (VIRTUAL CO PHYSICS SRL, 2025)
Recently, cubic SnS shows promising potential for optoelectronic applications, including solar cells. Despite its advantages, the photoelectrochemical (PEC) properties of cubic SnS photoelectrodes remain underexplored. This study examines the PEC performance of cubic SnS photocathodes synthesized on FTO substrates via chemical bath deposition and annealed at 250(degrees)C for varying durations (10, 20, and 30 min). The as-deposited SnS films, characterized by a cubic crystal structure (lattice parameter: 1.162 nm, crystallite size: 17 nm), an energy gap of 1.75 eV, and an initial photocurrent of 0.8 mA/cm(2) at -1 V vs. Hg/HgO, showed significant enhancement upon annealing. A 10-minute annealing improved grain size and boosted the photocurrent to 1.4 mA/cm(2), while 20 minutes yielded optimized grain growth and secondary SnS2 phase, reducing performance. These findings highlight the importance of controlled annealing for optimizing cubic SnS PEC performance.